Training for professional judgment in accounting education - Ospina Delgado, Julieth; Giraldo Villano, Ximena (Cuadernos de Administración, 2020)
The global convergence process towards International Financial Reporting Standards supported by multilateral agencies such as the World Bank poses a challenge to accounting education’s ability to make judgments and estimates, due to the emphasis placed on general new principles-based regulation instead of detailed rules. The international literature has highlighted this aspect amply, while in Colombia, it remains incipient. This paper aims to analyze the approach to professional judgment and critical thinking in the educational proposals of high-quality Public Accounting programs in Colombia as a factor contributing to the formation of such judgment in the accountant. This paper provides empirical evidence based on a qualitative-documentary methodology, which analyzes the Educational Projects provided by accredited universities. Among the most relevant findings is the lack of an explicit statement about pedagogical strategies to materialize a professional judgment that some of the universities analyzed mentioned succinctly.